Optimization of the DNA isolation procedure for assessing the genetic diversity of essential oil roses (Rosa L.) - S. B. Seitadzhieva; S. Z. Guchetl; S. V. Didovich; E. V. Gorodnyaya (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. High content of organic compounds that worsen nucleic acid purification in aromatic plants, as well as the use of such toxic substances as phenol and mercaptoethanol in many protocols for plant DNA isolation, make it advisable to take the above disadvantages into account when optimizing the DNA extraction technique for the work with essential oil rose plants. Material and methods. Rose accessions from the Crimean Federal University’s Botanical Garden, and those from the collection held by the Research Institute of Agriculture of Crimea were included in the study. DNA extraction was done according to a modified CTAB protocol. Effectiveness of the technique was assessed using spectrophotometry, horizontal electrophoresis, and ISSR-PCR. Results. DNA preparations extracted with the modified technique were well visualized on the electropherogram and demonstrated high spectrophotometric values. DNA content was twice as high in preparations isolated with an extraction buffer with PVP, compared to a PVP-free buffer. The concentration was also higher in DNA extracts from stems than that from leaves. Purity parameters expressed by the absorption ratios at wavelengths A260/280 and A260/230 were again higher for DNA extracts from stems isolated with an enriched buffer, the A260/230 ratio falling within the normal range only in DNA extracted from stems in the presence of PVP. Besides, DNA extracts were effectively purified from proteins without phenol or mercaptoethanol, due to double rinsing with a chloroform/isoamyl alcohol (24 : 1) mixture. Conclusion. Using rose stem tissues as the research material, adding 2% PVP to the extraction buffer, and twofold rinsing with a chloroform/isoamyl alcohol mixture made it possible to obtain DNA extracts with high concentrations and purity indices within normal ranges suitable for the ISSR analysis of essential oil rose genetic diversity.